Short-Course Rather Than Low-Dose Amphotericin B May Exert Potential Influence on Mortality in Cryptococcal Meningitis Patients Treated With Amphotericin B Plus Flucytosine Alone or in Combination With Fluconazole - Xu, Lijun; Tao, Ran; Wu, Jingjing; Dai, Xiahong; Hu, Caiqin; Huang, Ying; Chen, YaoKai; Zhu, Biao; He, Jianqin (Frontiers in Microbiology, 2019)
Background The influence of Amphotericin B (AmB) dose and the addition of fluconazole (Flu) on the AmB + 5-flucytosine (5FC) regimen for cryptococcal meningitis (CM) treatment remain debatable. Methods A retrospective study was conducted to compare 44 CM patients treated with AmB + 5FC and 78 CM patients treated with AmB + 5FC + Flu using the propensity score matching method. The effects of AmB dosage, AmB course and Flu addition on the cerebrospinal fluid (CSF) chemical profile recovery, adverse effects, and 90-day mortality were compared between the groups. Results No differences in adverse effects, the rate of the 14-day CSF chemical profile recovery and 90-day cumulative survival rate (91.2% vs. 87.5%, P = 0.637) were observed between the AmB + 5FC group and the AmB + 5FC + Flu group. However, the incidence rates of hypokalemia (33.9%) and creatinine elevation (7.1%) in patients treated with an AmB dosage of 0.4–0.5 mg/kg/d were less than those (53.0 and 22.7%, respectively) treated with an AmB dosage of 0.6–0.7 mg/kg/d (P = 0.034 and P = 0.018, respectively). The 90-day cumulative survival rate was 70.1% for patients treated with AmB for <14 days and 96.4% for patients treated with AmB for ≥14 days (log-rank P < 0.001). Multivariate Cox proportional hazards models suggested the hazard ratio was 26.8 (95% CI: 3.9–183.2) for patients treated with AmB < 14 days than those treated with AmB ≥ 14 days (P = 0.001). Conclusion Treatment with AmB less than 14 days was associated with a higher 90-day mortality in CM patients. A relative lower dosage but prolonged course of AmB in the +5FC ± Flu regimen led to favorable trends of fewer adverse effects and comparable clinical efficacy.